Fractal noise : - Paolini, Christopher (Fractalverse, 2023)
"A new blockbuster science fiction adventure from world-wide phenomenon and #1 New York Times bestseller Christopher Paolini, set in the world of New York Times and USA Today bestseller To Sleep in a Sea of Stars. July 25th, 2234: The crew of the Adamura discovers the Anomaly. On the seemingly uninhabited planet Talos VII:a circular pit, 50 kilometers wide. Its curve not of nature, but design. Now, a small team must land and journey on foot across the surface to learn who built the hole and why. But they all carry the burdens of lives carved out on disparate colonies in the cruel cold of space. For some the mission is the dream of the lifetime, for others a risk not worth taking, and for one it is a desperate attempt to find meaning in an uncaring universe. Each step they take toward the mysterious abyss is more punishing than the last. And the ghosts of their past follow. "--